2016
DOI: 10.1080/08927014.2016.1221946
|View full text |Cite
|
Sign up to set email alerts
|

The quorum sensing molecule N-acyl homoserine lactone produced by Acinetobacter baumannii displays antibacterial and anticancer properties

Abstract: Secretory N-acyl homoserine lactones (AHLs) mediate quorum sensing (QS) in bacteria. AHLs are shown to be inhibitory for an unrelated group of bacteria and might mimic host signalling elements, thereby subverting the regulatory events in host cells. This study investigated the AHL produced by Acinetobacter baumannii and analysed its effect on other bacterial species and mammalian cells. Chemically characterized AHL had an m/z value of 325 with a molecular formula C18H31NO4 and showed its inhibitory potential a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 46 publications
0
14
1
Order By: Relevance
“…Lactones generally are microbial volatiles; volatile butyrolactones exhibit antibacterial activity [87]. Homoserine lactones are a widely distributed class of quorum sensing molecules, for some of which antibacterial properties were reported [88]. Burkholderic acid is a polyketide synthase-derived cytotoxic siderophore that exhibits antibacterial activity [89,90].…”
Section: Resultsmentioning
confidence: 99%
“…Lactones generally are microbial volatiles; volatile butyrolactones exhibit antibacterial activity [87]. Homoserine lactones are a widely distributed class of quorum sensing molecules, for some of which antibacterial properties were reported [88]. Burkholderic acid is a polyketide synthase-derived cytotoxic siderophore that exhibits antibacterial activity [89,90].…”
Section: Resultsmentioning
confidence: 99%
“…The C12-HSL and C12-oxo-HSL also decreased the levels of putrescine in human epidermal cells (HaCat) and, consequently, decreased the rate of cell proliferation [ 117 ]. John et al [ 118 ] showed that N -3-oxo-tetradecanoyl-homoserine lactone (3-oxo-C14-HSL) produced by Acinetobacter baumannii had a dose-dependent cytotoxic effect on human cervical cancer cells (HeLa), adenocarcinoma human alveolar basal epithelial cells (A549), Dukes’ type C colorectal adenocarcinoma cells (HCT15) and Dukes’ type B colorectal adenocarcinoma cells (SW480), with induction of apoptosis and reduced viability and proliferation of these cells in the presence of AHL. In addition, these authors showed that 3-oxo-C14-HSL was able to decrease the growth of Staphylococcus aureus .…”
Section: Resultsmentioning
confidence: 99%
“…found that none of them produced hydroxyl C12. Chan et al [9] and John et al [42] who worked on A. baumannii 4KT and A. baumannii AB 14, respectively, also did not detect hydroxyl C12 using LCMS analysis.…”
Section: Discussionmentioning
confidence: 99%